Factors influencing resilience of parents with children with neurodevelopmental disorders: The role of structural language, social cognition, and social support - Flores-Buils, Raquel; Andrés-Roqueta, Clara (Frontiers in Psychiatry, 2022)
Background Resilience allows a more positive coping and improves parents' wellbeing when they face a difficult situation like having a child with a neurodevelopmental disorder (NDD). We aim to analyze the development of resilience in parents of children with different NDD (ASD, DLD and ADHD) with different levels of structural language and social cognition, as well as the social support available for their families, and compare it to children with typical development (TD). Method We analyzed the level of resilience of 156 parents, 73 with children with TD and 73 with three different NDD, taking into account variables such as age, structural language (receptive grammar) and social cognition (emotional understanding) of the children, and also the type of social support available to them. Results Children with DLD and ASD showed lower receptive grammar and emotional comprehension skills, although only parents of children with ASD obtained better resilience scores. Moreover, age of children and formal support variables predicted the resilience of the parents according to the type of NDD. Discussion The severity of social cognition and structural language difficulties of children with NDD and the fact of having support from professionals and family associations have a significant influence on the development of parental resilience.